2017
DOI: 10.1021/acssuschemeng.7b01940
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Automotive Ammonia Fuel Cycle Using P-Graphs

Abstract: Ammonia is a potential low-carbon alternative automotive fuel. However, it is produced commercially via the energy-and greenhouse gas-intensive Haber−Bosch process, and its nitrogen footprint may also detract from its environmental benefits. Thus, whether its use as an automotive fuel is sustainable from a life-cycle standpoint remains in question. In this study, a P-graph model is developed to determine the best well-to-wheel pathway for the use of ammonia as an automotive fuel, using carbon and nitrogen foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…12 Ammonia can be used as a fuel in internal combustion engines, although this causes pollution unless optimized. 13 Ammonia can also be used near where it is generated as a fertilizer. While this fertilizer is a key to the "Green Revolution", 14 it is separate from using ammonia as a means of storing and transporting wind energy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Ammonia can be used as a fuel in internal combustion engines, although this causes pollution unless optimized. 13 Ammonia can also be used near where it is generated as a fertilizer. While this fertilizer is a key to the "Green Revolution", 14 it is separate from using ammonia as a means of storing and transporting wind energy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ammonia serves as a carrier for hydrogen, which can be used in fuel cells . Ammonia can be used as a fuel in internal combustion engines, although this causes pollution unless optimized . Ammonia can also be used near where it is generated as a fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The world’s ever increasing energy demand associated with the adverse effects of existing fossil fuels directed immense research activities toward the design and development of clean and renewable energy devices, which are capable of harvesting green energy from sustainable energy sources. Recently, glucose fuel cells (GFCs) have emerged as an excellent green energy device, as it is able to offer considerable power output via the glucose oxidation reaction (GOR) and oxygen reduction reaction (ORR) at the anode and cathode, respectively. , However, the development of high performance GFCs is substantially hindered by the sluggish GOR and ORR kinetics, prohibitive production cost, and limited durability, which are mostly associated with the existing anode and cathode catalysts of GFCs.…”
Section: Introductionmentioning
confidence: 99%
“…To address this need, a few life cycle assessment and life cycle optimization studies have been done to address possible trade-offs in the use of ammonia as a fuel. Angeles et al (2017) computed and compared nitrogen and carbon footprints of either fuel cell or internal combustion engine vehicles fed with ammonia or ammonia-diesel/gasoline combinations. It was found that a fuel cell vehicle fed with ammonia from the cyanobacteria-based process proposed in Razon (2014) gave both the lowest nitrogen footprint and the lowest carbon footprint.…”
Section: Introductionmentioning
confidence: 99%